Spontaneous Rupture of the Urinary Bladder Presenting as an Acute Abdomen: A Rare Case Report - Gordon Putota; Andrew Mpagwuni Ziblim; Bentil Awe Wewoli (Clinical Case Reports)
ABSTRACT Urinary bladder rupture is uncommon. When it occurs, it is usually traumatic or iatrogenic. Rarely, this rupture is spontaneous, and its presentation poses diagnostic challenges that require a high index of suspicion. We present a rare case of a spontaneous bladder rupture presenting as peritonitis that was diagnosed at laparotomy.